2019
DOI: 10.1108/ijbm-11-2018-0309
|View full text |Cite
|
Sign up to set email alerts
|

How does P2P lending platform reputation affect lenders’ decision in China?

Abstract: Purpose The purpose of this paper is to examine how the impact of Chinese peer-to-peer (P2P) platform reputation directly and indirectly (mediate effect) affects investors’ (lenders) investment choices. Design/methodology/approach Using data collected from 478 P2P platforms, this paper calculates platform reputation via a β function after establishing a reputation mechanism by game analysis. This is followed by testing both the direct effect of platform reputation on investors’ investment choices (proxying b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 35 publications
1
15
0
Order By: Relevance
“…The third section of the questionnaire is to collect data on the awareness of the eleven P2P lending platforms. Questions related to the main characteristics of P2P lending given in Shi, Wu, and Hollingsworth (2019) are used to test the awareness of P2P lending platforms in Malaysia. After filtering and validating the collected data, answers from only 65 respondents are used for the analysis.…”
Section: Methodsmentioning
confidence: 99%
“…The third section of the questionnaire is to collect data on the awareness of the eleven P2P lending platforms. Questions related to the main characteristics of P2P lending given in Shi, Wu, and Hollingsworth (2019) are used to test the awareness of P2P lending platforms in Malaysia. After filtering and validating the collected data, answers from only 65 respondents are used for the analysis.…”
Section: Methodsmentioning
confidence: 99%
“…Due to the information asymmetry, if P2P platforms deliberately hide critical information (e.g. the true operational status of P2P platforms) or take risky behaviors to make profits at the cost of the lenders' investments (Shi et al , 2019), lenders will face more significant risks (Lee and Lee, 2012). However, although lenders are aware of the multifarious risks, they still decide to participate in the investment in P2P lending.…”
Section: Research Model and Hypothesesmentioning
confidence: 99%
“…Ding et al proved that there was an effective reputation mechanism in the P2P lending market by analyzing the transaction data of 78,000 borrowers in the P2P lending platform "renrendai.com" [17]. Shi et al found that the reputation of the P2P lending platforms played a direct or indirect role in investors' investment choices [18]. Davies and Giovannetti pointed out that reputation played an important role in the success of crowd-funding projects [19].…”
Section: Literature Reviewmentioning
confidence: 99%
“…First, most of the existing literature mainly focuses on the reputation of borrowers and investors in the IFP. ey pay more attention to the mechanism [14][15][16][17][18][19], influencing factors [20][21][22], and the measurement of reputation [23].…”
Section: Introductionmentioning
confidence: 99%